A Robust CDMA VLC System Against Front-End Nonlinearity - H. Qian; S. C. Dai; S. Zhao; S. Z. Cai; H. Zhang (IEEE Photonics Journal, 2015)
The nonlinearity of a light-emitting diode (LED) limits the system performance of a visible light communications (VLC) system. Many nonlinearity mitigation methods have been studied. Recent technology advances in the micro-LED array have provided a simple alternative to deal with the system nonlinearity. In this paper, we study the approach of providing multiple access for the VLC system with the micro-LED array. A code-division multiple-access (CDMA) scheme that enables multiple access with variable data rate is proposed. In addition, the proposed system architecture is immune to the nonlinearity of the micro-LED array, thus providing optimal system performance. Simulations and laboratory experiments show the robustness and consistency of the proposed scheme.